If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(2x + -1) = 9x + 2(2 + -1x) Reorder the terms: 6x + -1(-1 + 2x) = 9x + 2(2 + -1x) 6x + (-1 * -1 + 2x * -1) = 9x + 2(2 + -1x) 6x + (1 + -2x) = 9x + 2(2 + -1x) Reorder the terms: 1 + 6x + -2x = 9x + 2(2 + -1x) Combine like terms: 6x + -2x = 4x 1 + 4x = 9x + 2(2 + -1x) 1 + 4x = 9x + (2 * 2 + -1x * 2) 1 + 4x = 9x + (4 + -2x) Reorder the terms: 1 + 4x = 4 + 9x + -2x Combine like terms: 9x + -2x = 7x 1 + 4x = 4 + 7x Solving 1 + 4x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 1 + 4x + -7x = 4 + 7x + -7x Combine like terms: 4x + -7x = -3x 1 + -3x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 1 + -3x = 4 + 0 1 + -3x = 4 Add '-1' to each side of the equation. 1 + -1 + -3x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 4 + -1 -3x = 4 + -1 Combine like terms: 4 + -1 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| -5x+y=-10 | | -3(f+2)+-2=4 | | -3=3(q+3)-6 | | 8w+2w-5=15 | | 100x(x-3)=450-50 | | 2x(4x-1)+3=18 | | 8p+2p-5p+2=17 | | 6x^4+13x^2-5=0 | | 27x^3-3443=0 | | k^2-7k-18=0 | | 6x^4-17x^2-28=0 | | 5(V-6)=8V-33 | | 5(5n-9)=n+3(18n+5) | | x-y=40 | | 5x-x=32 | | 11v-7(6v+20)=v+20 | | 18x^2-15x-18=0 | | -3w+5(-5w+19)=-2-20-19w | | 22=6(x+7)+4x | | x-4/2=11 | | cx^2-cy^2+dx^2-dy^2= | | e^2x+1=300 | | 2(4+20d)=-4(13+5d) | | ab^2-2ab-35a= | | 20-20u+16=-18u-2(10u+18) | | 7(m-2)+4(m+6)= | | 5(x-1)-2(x-7)=4(x+2) | | -4x-3=45 | | y^4+2y^2+1= | | 6(3c+5)-16c=8c | | 5(x+1)-1(x-7)=4(x+2) | | x/3+10=-3 |